A kind of lithium slag unburned ceramsite filter material and preparation method thereof
By grinding lithium slag in a cone rotary grinder and combining it with high silicon materials, steam maintenance and shaping strengthening methods are used to solve the problems of low utilization rate and high-temperature firing in the preparation of lithium slag ceramic materials, and the problem of low utilization rate and high-temperature firing is required. High strength and good wear resistance to burn-free ceramic filter material.
Patent Information
- Application Number
- CN202310914762.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-25
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2043-07-25
AI Technical Summary
In the prior art, the use of lithium slag to prepare ceramic materials has problems such as difficult raw materials to be obtained, low utilization rate of lithium slag, high temperature firing, or poor product performance.
The lithium slag is ground by a cone rotary grinder, combined with high silicon materials, cement, quicklime, settling agent, air emitting agent, nano-enhancing agent, foam stabilizer and water, and the burn-free ceramic particles are prepared through steam curing and plasticizing strengthening. Filter material.
The efficient utilization of lithium slag is achieved, and the prepared ceramic filter material has the advantages of high strength, good wear resistance, green and low carbon, and does not require high temperature firing.
Smart Images

Figure CN117164319B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to ceramic materials, in particular to ceramic particles using lithium slag as raw material and a preparation method thereof. Background Art
[0002] Lithium slag is waste residue produced during the processing of lithium-containing ores such as spodumene and lepidolite. With the mining and processing of lithium resources, the output of lithium slag has increased dramatically. At present, the means of effective resource utilization of lithium slag are very limited. There are schemes for preparing ceramic materials using lithium slag in the prior art, but these schemes have problems such as difficult access to raw materials, low utilization rate of lithium slag, high temperature firing or poor product performance. For example, the Chinese patent document with publication number CN115286419A records a lightweight ceramsite made from lithium slag extracted by sulfuric acid method and its preparation method and application, wherein the raw materials containing lithium slag extracted by sulfuric acid method, additive A and additive B are granulated to obtain pellets, and then the pellets are roasted to obtain; the additive A contains magnesium carbonate and calcium carbonate; the additive B is at least one of sodium feldspar and potassium feldspar. For another example, a Chinese patent document with publication number CN102125786A records a method for preparing a porous ceramsite filter material using lithium-extracted slag from lepidolite, the method comprising: (1) preparing a mother ball of Φ 1-2 mm from the pressure-impregnated lithium slag and clay powder in a mixer; (2) rolling the mother ball into spherical particles of Φ 3-10 mm in a granulator; (3) feeding the material ball into a pre-burning section of a rotary kiln for pre-burning at 200-500° C. for 10-20 minutes, and then entering a firing zone for calcining at 1050-1180° C. for 10-30 minutes; (4) the hot material ball after exiting the kiln can be cooled by a cooler or cooled naturally to obtain the product. For another example, a Chinese patent document with publication number CN102126838A records a method for preparing lightweight building material ceramsite using lithium slag extracted from lepidolite, the method comprising: (1) mixing pressure-leached lithium slag with a water content of no more than 30%, clay powder and a pore-forming agent in a ratio of 70-80 parts by weight: 10-30 parts by weight: 1-5 parts by weight, stirring into loose particles to form mother balls; (2) sending the mother balls of step (1) to a ball-forming device, spraying a ball-forming binder to make the mother balls roll larger to form spherical particles with a diameter of 5-30 mm; (3) calcining the material balls obtained in step (2), the calcination temperature is 1100-1200° C., and the calcination time is 25-40 minutes; (4) cooling the hot material balls after calcination out of the kiln, and obtaining the material balls.
[0003] Therefore, the technology of using lithium slag to prepare ceramic materials needs further research. Summary of the invention
[0004] In view of this, the present invention provides a lithium slag unfired ceramsite filter material and a preparation method thereof, which at least solves a problem existing in the prior art.
[0005] The invention provides a lithium slag unfired ceramsite filter material, comprising the following raw materials in parts by weight: 5-30 parts of lithium slag, 40-60 parts of high silicon material, 6-15 parts of cement, 10-20 parts of quicklime, 3-5 parts of setting agent, 0.02-0.04 parts of gas generating agent, 0.2-0.4 parts of nano-enhancer, 0.05-0.10 parts of foam stabilizer and 90-150 parts of water.
[0006] In some preferred embodiments, the total mass fraction of silicon dioxide, aluminum oxide and iron oxide in the lithium slag is ≥55%, and the loss on ignition is ≤5%.
[0007] In some preferred embodiments, the high-silicon material is one or a mixture of several of quartz powder, natural sand and fluorite tailings.
[0008] In some preferred embodiments, the cement is ordinary Portland cement or R-type general-purpose Portland cement with a strength grade not less than 42.5.
[0009] In some preferred embodiments, the total mass fraction of calcium oxide and magnesium oxide in the quicklime is ≥65%, the digestion speed is ≤15min, and the digestion temperature is ≥60°C.
[0010] In some preferred embodiments, the setting regulator is one or a mixture of natural dihydrate gypsum, desulfurized gypsum, and phosphogypsum.
[0011] In some preferred embodiments, the gas generating agent is aluminum powder paste, sodium bicarbonate or a mixture thereof.
[0012] In some preferred embodiments, the nano-enhancing agent is wollastonite, nano-calcium carbonate, or a mixture thereof.
[0013] In some preferred embodiments, the foam stabilizer is one or a mixture of calcium stearate, polyacrylamide, and cellulose ether.
[0014] The present invention also provides a method for preparing the lithium slag unfired ceramsite filter material, the preparation method comprising the following steps:
[0015] grinding lithium slag;
[0016] The ground lithium slag is mixed with high silicon material and water to form a slurry;
[0017] The slurry is mixed with cement, quicklime, a setting regulator, a foam stabilizer, a nano-enhancer, and water to prepare a mixed slurry;
[0018] The gas generating agent is mixed with water and added to the mixed slurry, stirred evenly, cured at 50-60° C., cut into blocks, and steam cured at 100-200° C. to obtain a semi-finished ceramsite filter material;
[0019] The semi-finished ceramsite filter material is shaped and strengthened in a rotary grinder to obtain the lithium slag unfired ceramsite filter material.
[0020] Due to the adoption of the above technical scheme, the embodiments of the present invention have at least the following beneficial effects: the lithium slag unfired ceramsite filter material has the advantages of high strength, good wear resistance, and green and low carbon; the steam curing temperature adopted in the preparation method of the lithium slag unfired ceramsite filter material is within 200°C, and the ceramsite filter material can be obtained without firing. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Schematic diagram of a cone rotary grinder.
[0022] Explanation of reference numerals: 100, material inlet, 200, lining plate, 300, reverse grinding plate, 400, material outlet, 500, motor. DETAILED DESCRIPTION
[0023] The following will provide a clear and complete description of the concept and technical effects of the present invention in conjunction with the embodiments and drawings, so as to fully illustrate the purpose, scheme and effects of the present invention.
[0024] The present invention makes full use of silicon dioxide in lithium slag as a siliceous material, composites high-silicon materials, uses alkaline materials such as cement and quicklime as calcium materials, adds an appropriate amount of gas-forming agents such as aluminum powder paste as pore-forming agents, and an appropriate amount of functional additives such as coagulants, nano-enhancers, and foam stabilizers, and prepares unfired ceramsite filter materials through steam curing (temperature <200°C) and grinding and shaping with a cone rotary grinder. Compared with traditional sintered ceramsite filter materials (sintering temperature of about 1200°C), the preparation method of the present invention has the advantages of low production energy consumption and high waste utilization rate, and the prepared ceramsite filter material is a new green and low-carbon material.
[0025] The lithium slag unfired ceramsite filter material provided by the present invention mainly comprises lithium slag, high silicon material, cement, quicklime, setting regulator, gas generating agent, nano-enhancer, foam stabilizer and water as main raw material components, wherein the weight ratio of the components is lithium slag: high silicon material: cement: quicklime: setting regulator: gas generating agent: nano-enhancer: foam stabilizer: water = (5-30): (40-60): (6-15): (10-20): (3-5): (0.02-0.04): (0.2-0.4): (0.05-0.10): (90-150).
[0026] Among them, lithium slag can be the waste slag produced after lithium concentrate is calcined at high temperature by sulfate roasting method to extract lithium, and its total mass fraction of silicon dioxide, aluminum oxide and iron oxide is ≥55%, and the loss on ignition is ≤5%.
[0027] The high silicon material can be one or a mixture of quartz powder, natural sand, fluorite tailings, etc.
[0028] The cement may be ordinary Portland cement or R-type general purpose Portland cement with a strength grade not less than 42.5.
[0029] Quicklime can be in powder form, with calcium oxide as the main component, and the total mass fraction of calcium oxide and magnesium oxide is ≥65%, the digestion speed is ≤15min, and the digestion temperature is ≥60℃.
[0030] The setting regulator can be one or a mixture of natural dihydrate gypsum, desulfurized gypsum, phosphogypsum, etc. The main component of the setting regulator is calcium sulfate dihydrate, and the content of calcium sulfate dihydrate is required to be ≥75%.
[0031] The gas generating agent may be one of aluminum powder paste and sodium bicarbonate or a mixture thereof. The aluminum powder paste may be a water-based aluminum powder paste with a solid content of ≥65% and a fineness (0.075 mm sieve residue) of ≤3%.
[0032] The nano-enhancer can be one of inorganic materials such as ultrafine wollastonite, nano-calcium carbonate, etc., or a mixture thereof.
[0033] The foam stabilizer can be one of calcium stearate, polyacrylamide, cellulose ether or a mixture of several of them.
[0034] The main performance indicators of the lithium slag unfired ceramsite filter material are: the sum of the crushing rate and the wear resistance rate of the lithium slag unfired ceramsite filter material (C b ) is ≤6%, mud content C n ≤1%, with excellent wear resistance; specific surface area S w ≥0.5×10 4 cm 2 / g, has good adsorption performance.
[0035] The preparation method of the lithium slag unfired ceramsite filter material may include the following steps:
[0036] S100, grinding lithium slag;
[0037] S200, mixing the ground lithium slag with high silicon material and water to prepare slurry;
[0038] S300, mixing the slurry with cement, quicklime, setting agent, foam stabilizer, nano-enhancer and water to prepare a mixed slurry;
[0039] S400, mixing the gas generating agent with water and adding the mixture to the mixed slurry, stirring evenly, curing at 50-60° C., then cutting into blocks, and steam curing at 100-200° C. to obtain a semi-finished ceramsite filter material;
[0040] S500, shaping and strengthening the semi-finished ceramsite filter material in a rotary grinder to obtain the lithium slag unfired ceramsite filter material.
[0041] In step S100, the lithium slag can be ground to a specific surface area of ≥350 m 2 / g.
[0042] In step S200, high silicon material and water may be added to the ground lithium slag and stirred evenly to form slurry.
[0043] In step S300, cement, quicklime, setting regulator, foam stabilizer, and nano-enhancer may be added to the slurry and stirred for 60 to 90 seconds to prepare a mixed slurry.
[0044] In step S400, the gas generating agent can be first dispersed in water, then added to the mixed slurry, stirred evenly, poured into a mold frame, and cured at 50-60°C to reach cutting strength for cutting; then mechanical cutting is performed to form small blocks, and steam-cured at 100-200°C to obtain a semi-finished ceramsite filter material.
[0045] In step S500, the rotary grinder can be a conical rotary grinder. The conical rotary grinder has an inclination angle α of 10° to 20° with the horizontal plane, a taper of 3° to 5° in the grinding machine cylinder, a spiral belt with a grinding steel block inside, a wear-resistant lining plate arranged on the inner wall of the equipment, and a cone body with a reverse rotation direction to the spiral belt installed on the top of the spiral belt, which can enhance the grinding effect on the semi-finished ceramsite filter material. The interaction between the grinding block, the lining plate and the material is shaped and strengthened, screened and graded, and finally a ceramsite filter material finished product similar to a granular ball of different particle sizes is obtained.
[0046] Some typical embodiments are described below.
[0047] Example 1
[0048] Prepare lithium slag unburned ceramsite filter material according to the following steps:
[0049] (1) Dry the lithium mica residue and grind it to a specific surface area of 370 m² / g;
[0050] (2) Take 8 parts of lithium mica slag, 60 parts of quartz powder, add 40 parts of water to make a slurry;
[0051] (3) Add 10 parts of cement, 18 parts of quicklime, 4 parts of natural gypsum, 0.08 parts of cellulose ether, and 0.03 parts of wollastonite to the slurry, add 60 parts of water, and stir for 65 seconds to prepare a mixed slurry;
[0052] (4) Disperse 0.03 parts of aluminum powder paste in 2 parts of water, add it to the mixed slurry, and stir for 15 seconds; pour it into the mold frame and cure it (temperature is 55°C) for 1.5 hours to make it reach the cutting strength; cut it into small pieces and then steam cure it (temperature is 195°C) to obtain block-shaped semi-finished ceramsite filter material;
[0053] (5) After being shaped and strengthened by a conical rotary grinder, lithium slag unfired ceramsite filter material is obtained.
[0054] Example 2
[0055] Prepare lithium slag unburned ceramsite filter material according to the following steps:
[0056] (1) Dry the lithium mica residue and grind it to a specific surface area of 360m² / g;
[0057] (2) Take 10 parts of lithium mica slag, 57 parts of quartz powder and add 40 parts of water to make a slurry;
[0058] (3) Add 10 parts of cement, 18 parts of quicklime, 5 parts of natural gypsum, 0.08 parts of cellulose ether, and 0.03 parts of wollastonite to the slurry, add 60 parts of water, and stir for 70 seconds to prepare a mixed slurry;
[0059] (4) Disperse 0.03 parts of aluminum powder paste in 2 parts of water, add it to the mixed slurry, and stir for 10 seconds; pour it into the mold frame and cure it (temperature is 60°C) for 1.5 hours to make it reach the cutting strength; cut it into small pieces and then steam cure it (temperature is 195°C) to obtain block-shaped semi-finished ceramsite filter material;
[0060] (5) After being shaped and strengthened by a conical rotary grinder, lithium slag unfired ceramsite filter material is obtained.
[0061] Implementation Case 3
[0062] A lithium slag unfired ceramsite filter material and a preparation method thereof, comprising the following steps:
[0063] (1) Dry the lepidolite residue and grind it to a specific surface area of 380 m² / g;
[0064] (2) Take 15 parts of lithium mica slag and 52 parts of quartz powder, add 40 parts of water to make a slurry;
[0065] (3) Add 10 parts of cement, 18 parts of quicklime, 5 parts of natural gypsum, 0.08 parts of cellulose ether, and 0.03 parts of wollastonite to the slurry, add 60 parts of water, and stir for 90 seconds to prepare a mixed slurry;
[0066] (4) Disperse 0.03 parts of aluminum powder paste in 2 parts of water, add it to the mixed slurry, and stir for 15 seconds; pour it into the mold frame and cure it (temperature is 57°C) for 1.5 hours to make it reach the cutting strength; cut it into small pieces and then steam cure it (temperature is 195°C) to obtain block-shaped semi-finished ceramsite filter material;
[0067] (5) After being shaped and strengthened by a conical rotary grinder, lithium slag unfired ceramsite filter material is obtained.
[0068] Comparative Example 1
[0069] The difference between this comparative example and Example 1 is that wollastonite is not added.
[0070] Comparative Example 2
[0071] The difference between this comparative example and Example 1 is that no cellulose ether is added.
[0072] The products obtained in Examples 1 to 3 and Comparative Examples 1 to 2 were tested, and the test methods for the breakage rate, wear resistance rate, mud content, and specific surface area were performed in accordance with CJ / T 299-2008 standard.
[0073] The test steps for breakage rate and wear resistance are as follows: first weigh 100g of clean ceramsite filter material, place it in a metal cylinder, add 6 steel balls with a diameter of 8mm, oscillate on an oscillator with a stroke of 140mm and a frequency of 150 times / min for 15min, weigh the mass passing through the test sieve with an aperture of 0.5mm, and obtain the test results by calculation.
[0074] The test steps for mud content are as follows: first weigh about 500g of dry expanded clay filter material sample, add water and stir for 5 minutes, soak for 2 hours, pour the muddy water into a test sieve with a pore size of 0.08mm, repeat the operation until it is clean, dry the sample on the sieve to constant weight, and obtain the test result by calculation.
[0075] The specific surface area was tested by gas chromatography.
[0076] The test results are shown in Table 1.
[0077] Table 1 Performance test results of products obtained in Examples 1 to 3 and Comparative Examples 1 to 2
[0078]
[0079] It can be seen from Table 1 that the lithium slag unfired ceramsite filter material prepared by the present invention has higher wear resistance and adsorption performance, wherein the sum of the crushing rate and the wear resistance rate (C b ) is 4.3~4.6%, mud content C n About 0.71%, with excellent wear resistance; specific surface area S w About 0.6×10 4 cm 2 / g, has good adsorption performance. Compared with comparative example 1, the sum of the crushing rate and the wear resistance rate (C b ) was 0.5% lower and 10.4% lower; the mud content C n The specific surface area S of Example 1 is 0.16% lower and 18% lower, indicating that the addition of nano-enhancer can improve the mechanical properties of ceramsite filter material and reduce the breakage rate. w Height 0.06×10 4 cm 2 / g, which is 11% higher, indicating that the addition of foam stabilizer can improve the pore size distribution of ceramsite filter material, increase the specific surface area, and thus improve the adsorption performance of ceramsite filter material.
[0080] The terms "including" and "having" and any variations thereof in the specification and claims of the present application and the drawings are intended to cover non-exclusive inclusions. For example, a series of steps or units are included, or optionally, steps or units not listed are included, or optionally, other steps or units inherent to these processes, methods, products or devices are included.
[0081] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example.
[0082] Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. Mentioning "embodiment" in this article means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present embodiment application. The appearance of this phrase in various positions in the specification is not necessarily the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It can be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0083] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.
Claims
1. A lithium slag unfired ceramsite filter material, comprising the following raw materials in parts by weight: 5-30 parts of lithium slag, 40-60 parts of high silicon material, 6-15 parts of cement, 10-20 parts of quicklime, 3-5 parts of setting agent, 0.02-0.04 parts of gas generating agent, 0.2-0.4 parts of nano-enhancer, 0.05-0.10 parts of foam stabilizer, and 90-150 parts of water; wherein, The nano-enhancer is wollastonite, the foam stabilizer is cellulose ether; the total mass fraction of silicon dioxide, aluminum oxide and iron oxide in the lithium slag is ≥55%, and the loss on ignition is ≤5%; the high-silicon material is one or a mixture of quartz powder, natural sand and fluorite tailings.
2. The lithium slag unfired ceramsite filter material according to claim 1, characterized in that: The cement is ordinary Portland cement or R-type general-purpose Portland cement with a strength grade not less than 42.
5.
3. The lithium slag unfired ceramsite filter material according to claim 1, characterized in that: The total mass fraction of calcium oxide and magnesium oxide in the quicklime is ≥65%, the digestion speed is ≤15min, and the digestion temperature is ≥60°C.
4. The lithium slag unfired ceramsite filter material according to claim 1, characterized in that: The setting regulator is one or a mixture of natural dihydrate gypsum, desulfurized gypsum and phosphogypsum.
5. The lithium slag unfired ceramsite filter material according to claim 1, characterized in that: The gas generating agent is one of aluminum powder paste and sodium bicarbonate or a mixture thereof.
6. The method for preparing the lithium slag unburned ceramsite filter material according to any one of claims 1 to 5, comprising the following steps: grinding lithium slag; The ground lithium slag is mixed with high silicon material and water to form a slurry; The slurry is mixed with cement, quicklime, a setting regulator, a foam stabilizer, a nano-enhancer, and water to prepare a mixed slurry; The gas generating agent is mixed with water and added to the mixed slurry, stirred evenly, cured at 50-60° C., cut into blocks, and steam cured at 100-200° C. to obtain a semi-finished ceramsite filter material; The semi-finished ceramsite filter material is shaped and strengthened in a rotary grinder to obtain the lithium slag unfired ceramsite filter material.
Citation Information
Patent Citations
Method for preparing porous ceramsite filter material by using lepidolite extracted lithium slag
CN102125786A
Method for preparing light building material ceramsites by using lithium extraction slag of lithium mica
CN102126838A
Lightweight ceramsite prepared from sulfuric acid method lithium extraction slag as well as preparation method and application of lightweight ceramsite
CN115286419A
Unbaked ceramsite with steel slag and mineral waste residues and method for preparing unbaked ceramsite
CN108623278A
Unfired ceramsite and preparation method thereof
CN115321931A
Cited By
Preparation method and application of molybdenum residue-lithium residue composite adsorbent
CN122937761A